Power Reduction of acetic acid to the heavy metal of blood cockle (Anadara granosa) - Citra Sianipar; Edison '; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aimed to reduce levels of heavy metals contained in the body ofblood cockle (Anadara granosa) with acetic acid soaking method. The experimentaldesign used in this study is a randomized block design (RAK) with 4 levelstreatments, blood cockle without soaking, the addition of 5% acetic acid, 15% and25%. The highest reducing power contained in Pb with 25 % acetic acid soaking, theCu with 5 % acetic acid soaking, the metal Zn with 25 % acetic acid soaking and Cdmetal with 25 % acetic acid soaking. The highest organoleptic assessment containedin such a test is the 25 % acetic acid soaking (16.58), aroma aroma is in control(15.96) and the texture is in control (17.88) .Keyword : Power reduction, acetic acid , heavy metals , blood cockle